1992
DOI: 10.1111/j.1468-2982.1992.00380.x
|View full text |Cite
|
Sign up to set email alerts
|

Headache Following Carotid Endarterectomy: A Prospective Study

Abstract: The occurrence of headache in the 28 days following surgery was studied in 50 consecutive patients (14F and 36M, mean aged 70 years) who underwent carotid endarterectomy for atheromatous carotid stenosis. Thirty-one patients (62%) reported headache. Headache occurred in the first five days after surgery in 87% of cases. Its characteristics and temporal profile were highly variable but it was mostly bilateral (74%), mild or moderate (78%), requiring no treatment (77%). No correlation was found between the occur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 8 publications
2
9
0
1
Order By: Relevance
“…However, these headaches are classified as mild to moderate in most patients (78%). 24 Sudden onset of severe unilateral headache ipsilateral to the endarterectomy site was documented in only 5 patients in this study. In addition, most studies have not confirmed the diagnosis of CHS with cerebral hemodynamic data.…”
Section: Discussionmentioning
confidence: 59%
“…However, these headaches are classified as mild to moderate in most patients (78%). 24 Sudden onset of severe unilateral headache ipsilateral to the endarterectomy site was documented in only 5 patients in this study. In addition, most studies have not confirmed the diagnosis of CHS with cerebral hemodynamic data.…”
Section: Discussionmentioning
confidence: 59%
“…Cluster-like headache was described to occur frequently in 2 studies [6,7], but in more recent studies, it was not observed at all [4,5]. Therefore, the incidence of this headache seems lower than described in the ICHD-IIIB criteria [9], unless we assume considerable underreporting.…”
Section: Discussionmentioning
confidence: 65%
“…Albuquerque et al [4] and Tehindrazanarivelo et al [5] studied the occurrence of headache following CEA. They do not describe any patients who developed cluster headache or a cluster-like headache following CEA.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In other studies, headache was usually described as a severe, pulsatile, temporal, frontal or retro-orbital pain, mainly ipsilateral to the treated artery [5,54]. The frequency of any post-CEA headache may reach 62% [55]. We considered all severe headaches to be symptoms of HS, irrespective of the headache laterality.…”
Section: Discussionmentioning
confidence: 99%